2015
DOI: 10.1509/jppm.14.157
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sector Collaboration, Institutional Gaps, and Fragility: The Role of Social Innovation Partnerships in a Conflict-Affected Region

Abstract: The authors aim to contribute to the literature on subsistence marketplaces and the marketing field more generally by exploring social innovation partnerships in a fragile country characterized by institutional gaps, specifically considering the role of cross-sector collaboration in conflict-affected areas. The empirical setting consists of coffee partnerships in Eastern Congo (DRC), where the authors collected data from and about companies, NGOs and cooperatives, using both primary and secondary sources, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 76 publications
2
65
0
1
Order By: Relevance
“…At a macro level, the role of markets in peacemaking has remained undertheorized, and voices have called for research to fill this gap (Haufler 2015;Kolk and Lenfant 2015). Marketing scholars have highlighted that marketing systems are integral to war recovery and war prevention (e.g., Shultz 2007;Shultz et al 2005).…”
Section: Peacemakingmentioning
confidence: 99%
“…At a macro level, the role of markets in peacemaking has remained undertheorized, and voices have called for research to fill this gap (Haufler 2015;Kolk and Lenfant 2015). Marketing scholars have highlighted that marketing systems are integral to war recovery and war prevention (e.g., Shultz 2007;Shultz et al 2005).…”
Section: Peacemakingmentioning
confidence: 99%
“…In a sense this relates to a broader literature on political CSR (Scherer, Rasche, Palazzo, & Spicer, 2016), but more in-depth studies have shown how companies not only struggle with these issues, especially in the most problematic (fragile) contexts, but also try to navigate through them, together with other stakeholders, to improve living conditions of communities (e.g. Kolk & Lenfant, 2013, 2015b.…”
Section: Company Contributions To Local Developmentmentioning
confidence: 97%
“…It is characterized by many socio-economic, humanitarian and governance problems that are also found in other difficult settings in developing countries (those with so-called institutional gaps or voids, see e.g. Kolk & Lenfant, 2015b;Parmigiani & Rivera-Santos, 2015).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…We provide an overview here. In terms of products and businesses, and markets, research in this stream has examined a number of issues ranging from creation of markets (Abdelnour and Branzei 2007), to social entrepreneurship (Azmat, Ferdous and Couchman 2015), market orientation (Burgess and Nyajeka 2007), alliances and institutions (e.g., Kolk and Lenfant 2015). The approach for developing sustainable solutions for subsistence contexts requires an understanding of the needs, drivers, and larger context elements that determine consumer behavior.…”
Section: Developing Products and Enterprise Models For Subsistence Markmentioning
confidence: 99%
“…Our own efforts have generated four books, and more than 40 authored publications, and we have also edited roughly 60 refereed publications authored by scholars around the world through special issues, all profiled at this University of Illinois website: https://business.illinois.edu/subsistence/research/publications/. This community has worked in different continents around the world on topics ranging from theory to method, in urban, rural and tribal communities and post-conflict settings, using different perspectives, and studying consumption and entrepreneurship, individual and community empowerment, social and commercial enterprise development and, individual and institutional elements (Abdelnour and Branzei 2010;Jones-Christensen et al 2010;Kolk 2015;Lindeman 2014;Mandiberg 2012;Ozanne and Saatcioglu 2007;Ruth and Hsiung 2007;Toledo-Lopez et al 2012).…”
mentioning
confidence: 99%